3 Primary percutaneous coronary intervention in the belfast health and social care trust- are we meeting guideline directed targets?. (6th October 2022) - Mailey, J; Shannon, C; McNeice, A; Murphy, C
Abstract : Background: The European Society of Cardiology (ESC) recommend that if reperfusion is delivered within 120 minutes (min) of diagnosis, a primary percutaneous coronary intervention (PPCI) strategy is preferable to fibrinolysis for the treatment of ST-elevation myocardial infarction (STEMI). The target from diagnosis to reperfusion is ≤60 min in a PPCI centre and ≤90 min when the diagnosis is made outside of a PPCI centre. Methods: We conducted a retrospective study evaluating the achievement of targets in patients with STEMI in the Belfast Health and Social Care Trust (BHSCT). Patients accepted for PPCI during the same 4-month period (October to January) over 3 consecutive years were identified. This period was selected to evaluate the impact of both COVID-19 and a policy change for emergency inter-hospital transfers by the Northern Irish Ambulance Service (NIAS) in October 2021. Patients were identified using the BHSCT PPCI database. Timing data was obtained from NIAS and clinical outcomes from both the BHSCT NICOR database and NI electronic care record. The target for reperfusion was defined by the ESC STEMI guidelines (diagnosis to reperfusion ≤60 min in a PPCI centre and ≤90 min when diagnosed outside a PPCI centre). Clinical outcomes were compared in patients in whom targets were and were not achieved. The primary outcome was in-hospital cardiovascular (CV) mortality. The secondary outcome was the incidence of left ventricular systolic dysfunction (LVEF <50%). Results: A total of 835 patients were accepted for PPCI during the study time period. Timing data was available in 533 patients (64%). The reperfusion target was achieved in only 41.5% of patients. The year did not impact the overall achievement of this target (19/20 46.7%, 20/21 41.0% and 21/22 41.2%, p=0.47) ( table 1 ). The route of referral for PPCI significantly impacted the achievement of the reperfusion target (NIAS 62.9%, PPCI centre 25.0%, non-PPCI centre 22.9%, p<0.001). The median time from diagnostic ECG to reperfusion with NIAS= 84 min (range 24–389 min), PPCI centre= 80 min (range 37–231 min) and non-PPCI centre= 115 min (range 20–685 min). Reperfusion within 120 min was achieved in 74.9% of patients. Achievement of reperfusion within 120 min was not impacted by year, but was lower in patients presenting to a non-PPCI centre (NIAS 91.6%, PPCI centre 83.0% and non-PPCI centre 54.7%, p <0.001). Table 2 demonstrates a comparison of baseline demographics in patients in whom the target for reperfusion was achieved (n=235) vs those not achieved (n=314). The primary outcome occurred in 2.1% of patients in whom the reperfusion target was achieved vs 5.7% of patients in whom the reperfusion target was not achieved (p=0.04) ( figure 1 ). The incidence of LVSD was higher in patients in whom the reperfusion target was not achieved (69.5% vs 59.9%, p=0.04) ( figure 2 ). Conclusion: The majority of patients presenting with STEMI to the BHSCT during this period did not achieve the target time to reperfusion recommended by ESC. Failure to achieve this target resulted in both an increase in CV mortality and LVSD. More than a quarter of patients did not achieve reperfusion within a time interval whereby PPCI would be considered superior to fibrinolysis. A policy to improve time to reperfusion has not resulted in an improvement in the delivery of reperfusion therapy in patients presenting to a non-PPCI centre.